Effects of Cashback, Flash Sale, and Free Shipping on Impulsive Buying at Shopee Marketplace: Case Study on Students in Labuhanbatu University - Ervina, Gita; Simanjorang, Elida FS; Siregar, Nurintan Asyiah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This research aims to analyze the influence of variable cashback, flash sale, and free shipping on impulsive buying at Shopee marketplace. This study uses a quantitative research method, which uses tools of measurement or application to obtain statistical values. The number of samples in this research is 91. The sample was taken using a non- probability sampling technique, the type of sampling taken was purposive sampling, the sampling technique was to get one that matched the specified criteria. The analysis tool used is SmartPls 4.0 with the Partial Least Square (PLS) method. Based on the results of data analysis the authors conclude that cashback on impulsive buying has a negative and insignificant effect, then H1 rejected. The effect of the flash sale variable on impulsive buying has a positive and not significant effect, then H2 rejected. The free shipping variable has a positive and significant effect on impulsive buying, so H3 accepted.